Response of multi-cut fodder barley (Hordeum vulgare) to varying levels and N application under semi-arid condition of Rajasthan - MEENA, L R; MANN, J S; JAT, H S; CHAND, ROOP; KARIM, S A (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during winter (rabi) seasons of 2005 to 2007 at Avikanagar, Rajasthan to find out the effect of barley (Hordeum vulgare L.) with varying levels and times of N application under semi-arid condition of Rajasthan. Application of 90 kg N/ha recorded significantly higher growth-attributing characters and dry matter accumulation over other doses of nitrogen. Application of 90 kg N/ha gave significantly higher green fodder (32.01 tonnes/ha), dry forage (8.22 tonnes/ha) and grain yield (3.57 tonnes/ha) over 30 and 60 kg N/ha, respectively. Application of 90 and 60 kg N/ha resulted an increase of 22.22% and 11.38% green fodder, 13.07 and 7.57% in dry forage and 35.23% and 15.91% grain yield, respectively over the 30 kg N/ha. Nitrogen-use efficiency showed decreasing trend and the maximum nitrogen-use efficiency was recorded with 30 kg N/ha application (848.19). Nitrogen content and uptake, crude protein content and protein yield were increased progressively with successive levels of nitrogen levels. The B:C ratio was recorded highest with 90 kg N/ha (2.40) and significantly higher than 30 and 60 kg N/ha (2.23 and 2.34). Crude protein content (7.17%) and protein yield (545.09 kg/ha) was increased with successive times of nitrogen application and was found significantly higher with three splits of nitrogen application. The maximum net returns (` 16 895/ha) and B:C ratio (2.43) was recorded when nitrogen were applied as 1/3 N at sowing + 1/3 N at Crown root initiation+ 1/3 N at tillering.